**Q: Write the equation of y = -x ^{2} + 2x + 2 in the form of y = a(x-h)^{2} + k**

A: To do this, we are going to use a strategy called “completing the square” — a fairly complicated algebra 2 concept.

We are currently in the form y = ax^{2}+bx+c and we want to get to y = a(x-h)^{2} + k

First, let’s establish a, b, and c in our equation: y = -x^{2} + 2x + 2

a = -1, b = 2, c = 2

I will walk you through the steps on how to do the problem. At the end, I will provide some explanation behind the concept and the “why”.

Step 1) Divide the entire equation by “a”

So, divide everything by -1:

y = -x^{2} + 2x + 2

y/ -1 = (-x^{2} + 2x + 2) / -1

And simplify to get:

-y = x^{2} – 2x – 2

Step 2) “Complete the Square”

This step involves finding what number to add (or subtract) into the equation that will make the x terms factor nicely. To find this number, we follow a simple pattern:

Take 1/2 of the coefficient in front of the x term and then square it.

The coefficient in front of x is -2.

1/2 * -2 = -1

Square -1 to get +1.

The number we need to “Complete the Square” is +1.

Add this number to both sides of the equation (remember to do it to BOTH SIDES to keep the equation balanced). Also, add in by the x’s just for ease, like so:

-y + 1 = x^{2} – 2x + 1 – 2

So, our modified equation is:

-y + 1 = x^{2} – 2x + 1 – 2

Step 3) Factor the x terms:

We are now going to factor the part of the equation I’ve highlighted. The part we factor involves the x’s and the “complete the square” number that we added to the equation:

-y + 1 = x^{2} – 2x + 1 – 2

Factoring x^{2} – 2x + 1 gives (x – 1)(x – 1) OR (x – 1)^{2}

So, we now have:

-y + 1 = (x – 1)^{2} – 2

Step 4) Isolate y

We have finished the hardest part (completing the square)! Now, we just solve for y and we are done:

-y + 1 = (x – 1)^{2} – 2

Subtract 1 from both sides:

-y = (x – 1)^{2} – 3

Multiply everything by -1:

y = -(x – 1)^{2} + 3

And there it is! We have taken the original equation: y = -x^{2} + 2x + 2 and re-written it in a different form: y = -(x – 1)^{2} + 3

Some logic behind the process:

Completing the square is the process of figuring out “what number” is needed to add (or subtract) in the equation so that it will factor easily into something like (x-h)^{2}. Once we determine the number needed, we add it to both sides of the equation to maintain balance. Remember, we aren’t altering the actual equation, we are just changing its appearance. Once we found the correct number, the equation will factor the way we need it to.